PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, IKLIM DAN BUDAYA SEKOLAH TERHADAP KINERJA GURU DI PERGURUAN IBU PAWIYATAN TAMANSISWA YOGYAKARTA (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
The research aims at finding out the partially influence of principal’s leadership factor on the teacher’s performance, school climate on the teacher’s performance, school culture on the teacher’s performance, principal’s leadership, school climate and school culture on the performance of teachers of Ibu Pawiyatan Tamansiswa School in Yogyakarta.The population of this research is teachers of Kinder Garten, Elementary School, Junior School, Senior School and Vocational School Ibu Pawiyatan Tamansiswa in Yogyakarta with the number of teachers is 104. The sample of this research is 78 teachers of Ibu Pawiyatan Tamansiswa School in Yogyakarta. The data collecting technique used questionnaire to find out principal’s leadership, school climate, school culture, and teacher’s performance. The research method applied was descriptive. Testing technique of data analysis pre-requirements are normality test, linearity test, and multi-co-linearity test. Then it was continued by multiple regression.Based on the research, it can be concluded that: (1) the factors of Principal’s leadership, school climate, and school culture have positive and significant influence on the performance of teachers in Ibu Pawiyatan Tamansiswa School Yogyakarta, (2) principal’s leadership has positive and significant influence on the performance of teachers in Ibu Pawiyatan Tamansiswa Yogyakarta, (3) school climate factor has positive and significant influence on the performance of teachers in Ibu Pawiyatan Tamansiswa School Yogyakarta, (4) school culture factor has positive and significant influence on the performance of teachers in Ibu Pawiyatan Tamansiswa School Yogyakarta. Mean while the effective and relative contribution based on the result of hypothesis testing is: (1) the effective contribution of principal’s leadership on teacher’s performance is 10.85% and the relative contribution is 30.51%, (2) the effective contribution of school climate on teacher’s performance is 10,71% and the relative contribution is 30,12%, (3) the effective contribution of school culture on teacher’s performance is 14% and the relative contribution is 39,37%.